Preoperative radiation therapy for clinically resectable adenocarcinoma of the rectum. - Mendenhall, W M (1985)
This is an analysis of 71 patients with clinically resectable adenocarcinoma of the rectum treated with preoperative irradiation and surgery at the University of Florida from July 1975 through December 1981. Seven patients were found to have liver metastasis at surgery; six had a complete resection of their primary rectal lesion and one had an incomplete resection of the rectal tumor. The remaining 64 patients had no evidence of metastasis at the time of surgery and underwent a complete resection of their rectal cancer. In the early years of the trial, the maximum tumor dose consisted of 3000 to 3500 rad in 3.5 to 4 weeks; the dose was subsequently increased to 4500 rad in 5 weeks. Patients were taken to surgery between 2 and 11 weeks (mean, 3.5 weeks) following the completion of radiation therapy. All patients have a minimum follow-up of 3 years and 63% have a minimum follow-up of 5 years. The acute complications of treatment have been acceptable, with only one patient requiring a treatment rest for moist desquamation of the perineum. All patients completed the irradiation course and all were operated on. Pathologic examination of the surgical specimen revealed no tumor in 11%, and the incidence of positive lymph nodes was 19%, which was half the incidence of positive lymph nodes in a series of historical controls treated from 1959 to 1976 with surgery alone. Comparison of patients treated with preoperative irradiation and surgery with those treated with surgery alone revealed that the postoperative complications have been similar in incidence, distribution, and severity. There have been no postoperative deaths. The overall incidence of local-regional recurrence is 5/64 (7.8%), and the combined incidence of local-regional recurrence and/or distant metastasis is 18/64 (28%). The incidence of local-regional recurrence by preoperative dose is 3/23 (13%) for doses of 3000 to 3500 rad and 2/41 (5%) for doses of 4000 to 5000 rad. The 5-year local-regional failure rate is 3/40 (7.5%) for the group irradiated before surgery, and 39/135 (29%) for the historical controls managed by surgery alone (significance level = 0.015). The 5-year determinate disease-free survival is 27/38 (71%) for the patients irradiated before surgery, and 47/114 (41%) for the historical group of patients treated with surgery alone (significance level = 0.008).